THE COMPLEMENT SYSTEM AND GLOMERULAR KIDNEY DISEASES: ETIOPATHOGENESIS, DIAGNOSTICS AND TREATMENT - Cvetković, Milica D (Medicinski časopis, 2016)
ABSTRACT The human immune system consists of the innate and the acquired immunity. The complement system is part of the innate immune response and it can be activated through one of the three pathways: the classical pathway, the alternative pathway and the lectin pathway. Complement activation forms the C3-convertase complex. The C3-convertase proteolytically cleaves the C3 component into C3a and C3b fragments. The C3b fragment binds to the C3-convertase to form the C5-convertase. The C5-convertase is an enzyme complex that cleaves the C5 component into C5a and C5b fragments. The C5b component binds to C6, C7, C8, C9 thus forming the terminal complex of the complement activation – the membrane attack complex (MAC) which is responsible for effector functions of the complement system. The serum complement is a mediator of C3 glomerulopathy (C3G), a group of diseases that includes membranoproliferative glomerulonephritis type II (MPGN II) or dense deposit disease (DDD) and C3 glomerulonephritis (C3GN). These diseases are caused by a dysregulation of the alternative pathway of the complement activation system. The C3 nephritic factor (C3NeF) is an autoantibody to the alternative pathway C3-convertase, which can cause dysregulation of the pathway. Newly acquired knowledge has enabled therapeutic applications of a specific antibody to the C5 complement component (Eculizumab). Eculizumab is a recombinant monoclonal antibody that exhibits high affinity for the complement component C5, with the aim to inhibit its cleavage and activation of the terminal complement pathway. Key words: complement system, C3- glomerulonephritis, Eculizumab